2007
DOI: 10.3174/ajnr.a0771
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Symptomatic Intradural Vertebral Dissecting Aneurysms

Abstract: BACKGROUND AND PURPOSE:The purpose of this study was to report our experience with endovascular treatment of 14 patients with symptomatic intradural vertebral dissecting aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 22 publications
3
80
1
Order By: Relevance
“…During the past 10 years, there have been a significant number of investigations into the feasibility of this technique [1][2][3][4][5][6][7][8][9][10]. Some articles have described the stability of occlusions treated with detachable coils and the efficacy of providing protection against VAD recurrence and consequent bleeding [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past 10 years, there have been a significant number of investigations into the feasibility of this technique [1][2][3][4][5][6][7][8][9][10]. Some articles have described the stability of occlusions treated with detachable coils and the efficacy of providing protection against VAD recurrence and consequent bleeding [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional surgical treatment includes trapping the aneurysm, proximal ligation of the vertebral artery (VA ), or wrapping the aneurysm. Previous reports have suggested that endovascular parent artery occlusion is a safe and effective treatment for VAD [1][2][3][4][5][6][7][8][9][10]. Although some case series have reported on the feasibility of stent replacement, endovascular internal trapping has been performed in most of the cases.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the whole vertebral segment including the aneurysm is occluded with coils. 19 The contralateral vertebral artery will provide flow to the basilar artery, and the ipsilateral vertebral artery supplies the PICA. Only in patients with a single vertebral artery without patent posterior communicating arteries, is sparing the parent vessel mandatory.…”
Section: Vertebral Artery Occlusionmentioning
confidence: 99%
“…Most ruptured VBDAs can be treated by deconstructive treatments, which sacrifice the parent artery to obliterate the dissecting aneurysm. [1][2][3][4] However, how to manage a ruptured VBDA, which is not suitable for deconstructive treatment, is not well established. Also, there has been controversy on how to manage an unruptured VBDA.…”
mentioning
confidence: 99%